Does vocational education matter? evidence from a large-scale cross-sectional dataset in Indonesia - Arfrida Boedirochminarni; Salapudin Salapudin; FX Gugus Febri Putranto (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
This study investigates employment outcomes among recent graduates in Indonesia and examines the persistence of the vocational paradox, whereby vocational education does not translate into superior labor market absorption. Using nationally representative microdata from the 2023 National Labor Force Survey and a binary logistic regression framework, the analysis estimates the associations between educational pathway, gender, marital status, participation in job training, and the probability of employment. The results indicate that vocational graduates have a significantly lower likelihood of employment than their non-vocational counterparts, while participation in job training is positively associated with employment outcomes. Interaction effects suggest that training partially moderates sociodemographic disparities in labor market entry but does not eliminate the employment disadvantage associated with vocational education. Interpreted within an institutional framework of skill formation, these findings are consistent with structural constraints that hinder the translation of vocational credentials into employment outcomes, including limited coordination between education providers and firms and the restricted adaptability of training pathways.